Target’s Earnings Purity and M&A Premium: Evidence From China - Wenting Guo; Faqin Lan; Fang Zhang (SAGE Open)
This study introduces the concept of earnings purity, a novel construct in corporate finance, and investigates its impact on M&A premiums in China. Based on a multi-dimensional fixed-effects panel regression model, we find that higher earnings purity significantly increases M&A premiums by enhancing target firm valuation. To evaluate the rationality of using earnings purity as a basis for premium decisions, we analyze the opposing effects of information-sharing and information-exclusion, and then assess their relative strength by identifying a cubic S-shaped relationship between earnings purity and negotiation time. This pattern reveals a dynamic shift in the dominance of the two effects across different purity levels: information-sharing prevails at both low and high levels, while information-exclusion tends to dominate at moderate levels. It indicates that whether earnings purity serves as a primary basis for premium decisions depends on the capital market’s current earnings state. Heterogeneity analyses further show that the effect of earnings purity is more pronounced under adverse institutional conditions, for smaller targets, and in cross-border or inter-industry deals. These findings offer new empirical evidence on the role of earnings purity in M&A pricing and enhance our understanding of how earnings-based fundamentals contribute to the rationality of premium decision-making. JEL Classification: G34, G14, L2.